Diversity Tajdid Dan Konstruksi Islamic Studies - Anshori, Isa (Fakultas Agama Islam, 2016)
One of the largest religious organization in Indonesia is Muhammadiyah. Movement of religious organizations has attracted many people from various dsiplin science related to the characteristics and the vision of the progress of (modern) in the stretcher, various breakthroughs made by the Islamic organization Muhammadiyah in order to find an alternative solution to the problem of Muslims in Indonesia, especially in relation to Islamic ideology religious and social praxis.This research is the study of literature / literary using the method of philosophical analysis, because of the issues examined are related to epistemological aspects ijtihad and tajdid present in Muhammadiyah religious organizations in Indenesia, the approach taken is patterned historical-thematic.Ijtihad and tajdid that characterizes Muhammadiyah Muhammadiyah is as elan vital, especially at the beginning of its emergence in the nineteenth century AD, where Islam in Indonesia, especially Java suffused with various mythological takhayyul, khurofat and heresy, so that Islam should be a driving force of progress mankind (dynamic and liberating) instead became stagnant religion. Early emergence of Muhammadiyah regarded as a battering ram